Meteor! - Polacco, Patricia (New York : Dodd, Mead, 1987)
A quiet rural community is dramatically changed when a meteor crashes down in the front yard of the Gaw family.
*BOOKLIST*
4.0
K-3
Keywords: Meteors -- Fiction; Country life -- Fiction; Meteors -- Fiction; Country life -- Fiction